Rural India, the problem of Open Defecation and India’s Public Health Programs: Lessons in Social Learning - Chawla, Abhay (Nusantara Journal of Behavioral and Social Science, 2024)
Open defecation (OD) remains a significant public health and environmental challenge, particularly in rural India, where socio-economic and cultural barriers hinder the adoption of sanitation facilities. Despite over two decades of government initiatives, including the Total Sanitation Campaign (TSC), Nirmal Bharat Abhiyan (NBA), and Swachh Bharat Mission (SBM), achieving an Open Defecation Free (ODF) status has proven elusive. This paper examines the systemic limitations of these programs, focusing on the disconnect between policy objectives and community realities. Drawing from the author’s field experience in Haryana, the study highlights critical barriers, including inadequate water supply, economic constraints, and insufficient integration of social learning strategies. The analysis underscores the failure of top-down approaches that emphasize latrine construction while neglecting socio-cultural dynamics and local engagement. The lack of trained personnel, culturally relevant messaging, and participatory planning has resulted in low adoption rates and widespread skepticism about sanitation programs. Using Bandura’s social learning theory, the paper advocates for community-led approaches that leverage social networks and behavioral modeling to foster sustainable change. By comparing India's experiences with successful sanitation strategies in countries like Bangladesh, this study emphasizes the need for context-specific, inclusive, and adaptive solutions. The findings contribute to the broader discourse on public health, demonstrating that sustainable sanitation requires a holistic approach integrating technology, behavior change, and community ownership. Policymakers must prioritize cultural sensitivity and social learning to bridge the gap between infrastructure provision and behavioral adoption, ensuring long-term public health benefits.